2017
DOI: 10.1088/1674-4926/38/8/084006
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical simulation of performances in CIGS thin-film solar cells with cadmium-free buffer layer

Abstract: Copper indium gallium selenium (CIGS) thin film solar cells have become one of the hottest topics in solar energy due to their high photoelectric transformation efficiency. To real applications, CIGS thin film is covered by the buffer layer and absorption layer. Traditionally, cadmium sulfide (CdS) is inserted into the middle of the window layer (ZnO) and absorption layer (CIGS) as a buffer layer. However, the application of the GIGS/CdS thin film solar cells has been limited because of the environmental pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…This similarity is demonstrated not only on theoretical grounds by the polytype calculations presented here, but also by many experimental observations, such as the existence of wurtzite and sphalerite modifications in both ZnO and ZnS, which are in agreement with the calculations presented in this study. In support of this claim, we would also like to mention recent investigations that suggest the occurrence of theoretically proposed (Zafar et al, 2014;Luo et al, 2017;Goclon & Meyer, 2013;Iversen & Spencer, 2013), synthesized (Skinner & Barton, 1960;Patil et al, 2010;Chen et al, 2008;Shen et al, 2005;Homm et al, 2010;Wang et al, 2015) and natural (Š rot et al, 2003) polymorphs of ZnO intergrown with ZnS, as well as the great amount of research that has been performed on ZnO/ZnS heterostructures and heterojunctions (Wang et al, 2002;Yan & Xue, 2006;Hu et al, 2011;Jia et al, 2013;Sadollahkhani et al, 2014;Daiko et al, 2017;Giri et al, 2014;Tarish et al, 2017;Lu et al, 2009;Tian et al, 2014;Zhu et al, 2008 Sukkabot, 2017;Flores et al, 2018). Taken together, these are strong indications that the synthesis of at least some of the predicted mixed ZnO/ZnS compounds/modifications presented in this study should be possible.…”
Section: Structural Chemistry and Possible Synthesis Routessupporting
confidence: 65%
See 1 more Smart Citation
“…This similarity is demonstrated not only on theoretical grounds by the polytype calculations presented here, but also by many experimental observations, such as the existence of wurtzite and sphalerite modifications in both ZnO and ZnS, which are in agreement with the calculations presented in this study. In support of this claim, we would also like to mention recent investigations that suggest the occurrence of theoretically proposed (Zafar et al, 2014;Luo et al, 2017;Goclon & Meyer, 2013;Iversen & Spencer, 2013), synthesized (Skinner & Barton, 1960;Patil et al, 2010;Chen et al, 2008;Shen et al, 2005;Homm et al, 2010;Wang et al, 2015) and natural (Š rot et al, 2003) polymorphs of ZnO intergrown with ZnS, as well as the great amount of research that has been performed on ZnO/ZnS heterostructures and heterojunctions (Wang et al, 2002;Yan & Xue, 2006;Hu et al, 2011;Jia et al, 2013;Sadollahkhani et al, 2014;Daiko et al, 2017;Giri et al, 2014;Tarish et al, 2017;Lu et al, 2009;Tian et al, 2014;Zhu et al, 2008 Sukkabot, 2017;Flores et al, 2018). Taken together, these are strong indications that the synthesis of at least some of the predicted mixed ZnO/ZnS compounds/modifications presented in this study should be possible.…”
Section: Structural Chemistry and Possible Synthesis Routessupporting
confidence: 65%
“…In this study, we present the results of ab initio optimization of ZnO/ZnS polytypes, which provide alternatives to structural forms reported in the past, including bulk crystal structures, various nanostructures, heterostructures and heterojunctions. Surprisingly, little theoretical research is found in the literature (Zafar et al, 2014;Luo et al, 2017;Schrier et al, 2007;Hidalgo et al, 2010;Saha & Sarkar, 2013;D'Amico et al, 2016;Sukkabot, 2017;Flores et al, 2018) compared with the number of experimental investigations, and we hope that our investigation of polytypism in mixed ZnO/ZnS compounds will encourage future theoretical work in this field, suggest new opportunities for experimental synthesis and provide new materials with enhanced physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…CdS [41][42][43] Thickness The junctions of ITO with metal and/or semiconductor are considered ohmic. For simplicity, a perfect recombination junction is considered between PVK and FeSi 2 subcells that allows for an ideal series connection.…”
Section: Pvk Subcell Fesi 2 Subcellmentioning
confidence: 99%
“…For this purpose, various non-toxic and low-cost materials such as indium sulfide (In 2 S 3 ), indium (In)-doped zinc sulfide (ZnS: In), and zinc selenide (ZnSe) can be applied. ZnS: In is a promising buffer layer for TFSCs [ 15 , 16 ]. ZnS: In with a band gap of 3.1 eV [ 17 ] gives better performance than CdS with better lattice matching [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%